Discourse and Social Psychology, postmodernism, and capitalist collusion: An argument for more complex historiographies of psychology. (June 2015) - Wetherell, Margaret; Potter, Jonathan
Hayter and Hegarty argue that Discourse and Social Psychology (DSP) is a text sustaining late capitalism as surely as Taylorism sustained the Fordist capitalist epoch. In response, we first situate DSP in its intellectual context; second, highlight limitations in Hayter and Hegarty's use of Harvey's work on the history of capitalism; third, note the importance of analysing contexts and effects in genealogical research on psychology; fourth, show how the argument fails to clearly explicate different senses of reflexivity in DSP and; finally, consider the platform DSP built for the study of ideology and the implications for Hayter and Hegarty's own project. All of this highlights a need for psychologists to be more sophisticated in their historiography.